Acetone as an agent for PVDF recovery and delamination of lithium-ion battery electrodes - Jiang, Guozhan; Lee, David; Raimbault, David; Anderson, Paul A.; Leeke, Gary A. (Resources, conservation and recycling, 2024)
An acetone-based process to recover polyvinylidene fluoride (PVDF) from Li-ion battery electrodes has been developed. The PVDF binder was first dissolved away using acetone and the electrode material was subsequently subject to stirring in acetone for delamination from the current collector. The electrode became separated into electrode materials, PVDF binder, and current collector. The solubility of PVDF in acetone was measured as a function of temperature and was found to increase with temperature, reaching a maximum value at around 150 °C. The dissolution rate of PVDF both in its pure state and in electrodes was measured against temperature. The former was much faster than the latter. The diffusion of PVDF out of the electrodes was modelled mathematically for predicting the time for material recovery. The research demonstrates the potential of establishing a direct recycling process by enabling the recovery of PVDF, electrode materials and current collectors from Li-ion batteries. [Display omitted]